Discount shock, price-rent dynamics, and the business cycle - Jianjun Miao; Pengfei Wang; Tao Zha (Federal Reserve Bank of Atlanta, 2020)
The price-rent ratio in commercial real estate is highly volatile, and its variation comoves with the business cycle. To account for these two facts, we develop a dynamic general equilibrium model that explicitly introduces a rental market and incorporates the liquidity constraint on an individual firm's production as a key ingredient. Our estimation identifies the discount shock as the most important factor in driving price-rent dynamics and linking the dynamics in the real estate market to those in the real economy. We illustrate the importance of the liquidity premium and endogenous total factor productivity (TFP) in the nexus of the financial and real sectors.
Keywords: E22; E32; E44; 330; comovements; liquidity premium; stochastic discount factor; asset pricing; production economy; heterogenous firms; endogenous TFP; general equilibrium